Weighted school choice problems and the weighted top trading cycles mechanism - Stroh-Maraun, Nadja (Mathematical Social Sciences)
There are a number of school choice problems in which students are heterogeneous according to the number of seats they occupy at the school they are assigned to. We propose a weighted school choice problem by assigning each student a so-called weight and formulate the weighted top trading cycles algorithm (WTTC) to find a matching. The WTTC is strategy-proof and results in a Pareto efficient matching. While the WTTC is a robust extension of the TTC when weights are introduced, it is no longer guaranteed that each student gets a seat at a school even if the overall capacity exceeds the sum of weights. Additionally, the WTTC introduces a trade-off between weights and priorities as a student with a higher weight has a disadvantage to be matched to a particular school compared to a student with the same schools’ priorities but a smaller weight.
Keywords: Matching; School choice; College admission problems; Top trading cycles; Pareto efficiency; Strategy-proofness

An additive approach toward determination of liquid-phase mass transfer coefficients in sandwich packings - Franke, Patrick; Schlattmann, Ulrich; Devasthali, Oorv; Lutters, Nicole; Schubert, Markus; Hampel, Uwe; Iliuta, Ion; Larachi, Faïçal; Kenig, Eugeny (Chemical Engineering Science)

Teachers and trainers in dual vocational training as change agents for sustainable development!? – Questions on the professionalisation of in-company trainers and vocational school teachers - Hantke, Harald; Kiepe, Karina (Sustainability in Vocational Education and Training – National and International Experiences)

Pilot projects: Phenomena and key points of transfer of vocational education and training for sustainable development (VETSD) - Schlömer, Tobias; Kiepe, Karina; Rüdebusch, Gerrit; Günther, Niklas; Lieht, Jennifer (Sustainability in Vocational Education and Training – National and International Experiences)

Betriebliche Ausbilder:innen als Change Agents einer BBNE – Analyse und Reflexion im Spiegel der Ausbilderforschung - Schlömer, Tobias; Kiepe, Karina (Betriebliches Aus- und Weiterbildungspersonal im Fokus der Berufsbildungsforschung)

AnnoPy. Fachspezifische wissenschaftliche Textkompetenzen mit digitalen Medien in der Lehre fördern - Rezat, Sebastian; Rezat, Sara; Scholle, Oliver; Schulte, Carsten; Winkelnkemper, Felix (Lehrkräftebildung in der digitalen Welt. Zukunftsorientierte Forschungs- und Praxisperspektiven)
AnnoPy ist ein digitales Werkzeug, das an der Universität Paderborn in einer interdisziplinären Kooperation zwischen der Germanistischen Sprachdidaktik, Mathematikdidaktik und Informatikdidaktik entwickelt wurde, um wissenschaftliche Textkompetenzen zu fördern. Es kann in Präsenz- oder Blended-Learning-Szenarien eingesetzt werden, um eine Brücke zwischen individueller Auseinandersetzung mit dem Text und dessen sozial-diskursiver Aushandlung zu schlagen. Im Beitrag werden unterschiedliche Einsatzszenarien aus den drei beteiligten Disziplinen exemplarisch dargestellt, die jeweils unterschiedliche Facetten wissenschaftlicher Textkompetenz in den Mittelpunkt stellen. Im Fokus stehen dabei insbesondere die Förderung fachspezifischer Lesekompetenz im Rahmen einer Vorlesung mit großen Teilnehmendenzahlen sowie die Anwendung fachspezifischer Theorien und Konzepte in der Erschließung, Analyse und Beurteilung von Texten.
Keywords: digitale Medien; wissenschaftliche Textkompetenz; Lehrkonzept

Qualitative Analysis and Promotion the Language Acquisition of International Students at Universities in Germany: Opportunities and Challenges - Beutner, Marc; Lindenthal, Helene Maja; Lüttke, Jan-Phillip (Open Access Journal of Education & Language Studies)

Inter- and intragenerational differences in corrupt behavior: The development of morals after German reunification - Auer, Thorsten Fabian; Berg, Timo; Hoffmann, Christin (European Journal of Comparative Economics)
We investigate differences in bribing decisions among two generations from East and West Germany in a bribery game conducted as an online study (N=168). This way, we aim to explore moral considerations of individuals influenced by two formerly different institutional systems. We find a higher propensity to bribe among young Germans compared to the older generation. Young East Germans even reveal a slightly greater inclination to bribe than their West German counterparts. We conclude that preferences for personal favors may be induced among young East Germans given the tense relationship between market opportunities and conveyed cultural traits of a socialist imprint.
Keywords: Moral behavior; Corruption; Intra- and intergenerational study; Institutional transformation; Reunification

Liebestragödie. Genealogien einer französischen Gattung des 17. Jahrhunderts - Schlieper, Hendrik

Das Projekt "Schule für alle". Einblicke in ein Patenschaftsprojekt der universitären Lehrerbildung. - Kottmann, Brigitte; Pieper, Catania; Miller, Susanne

Forschungsstand zu Bewegung, Spiel und Sport im schulischen Ganztag in Deutschland: ein Scoping Review - Noetzel, Ida; Becker, Linda; Gräfin v. Plettenberg, Elisabeth; Kehne, Miriam (Forum Kinder- und Jugendsport)
Die Studienlage zum Thema Bewegung, Spiel und Sport im schulischen Ganztag in Deutschland zeigt sich vielseitig. Das Forschungsfeld ist neben wenigen umfassenden, überregionalen Studien durch kleinere Studien mit spezifischen inhaltlichen Schwerpunkten gekennzeichnet. Das vorliegende Scoping Review zielt darauf ab, die Erkenntnisse des Forschungsfeldes der circa vergangenen 20 Jahre zu systematisieren. Leitend ist die Forschungsfrage „Wie stellt sich der aktuelle Forschungsstand im Feld von Bewegung, Spiel und Sport im schulischen Ganztag in Deutschland dar?“ Auf Basis einer systematischen Literaturrecherche in fünf Datenbanken konnten aus 2365 Publikationen 52 in die Analyse eingeschlossen werden. Überwiegend wurden regionale Querschnittsstudien mit spezifischem Fokus durchgeführt. Die Studien befassen sich zumeist mit den Rahmenbedingungen von Bewegung, Spiel und Sport im Ganztag sowie mit den Charakteristika von Bewegung, Spiel und Sport im Ganztag. Die Analyse verdeutlicht unter anderem den Mangel an längsschnittlichen Studien sowie den Forschungsbedarf im Bereich der Qualität von Bewegung in diesem Setting.
Keywords: Review; Ganztag; Bewegung; Spiel; Sport; Forschungsstand

Electrocortical activity during resistance exercises in healthy young adults—a systematic review - Visser, Anton Samuel; Piskin, Daghan Yüksel; Büchel, Daniel; Baumeister, Jochen (Frontiers in Sports and Active Living)
Introduction Resistance training (RT) is known to induce both peripheral and central adaptations, resulting in enhanced strength, sports performance, and health benefits. These adaptations are specific to the training stimuli. The acute cortical mechanisms of single sessions resistance exercise (RE) are not yet understood. Therefore, this review investigates the electrocortical activity during acute RE regarding the specific RE stimuli. Methods A systematic literature search was conducted across three databases, focusing on the acute electrocortical activity associated with the muscle contraction type, load, and volume of RE in healthy young adults. Results Out of an initial 1,332 hits, 19 studies were included for data synthesis. The findings from these studies show that the RE load, contraction type, and volume during RE significantly affect brain activity. The current literature exhibits methodological heterogeneity attributed to variations in study quality, differences in the location of cortical sources, the cortical outcome parameter and the use of diverse training interventions. Discussion Despite inconsistencies in the current literature, this review highlights the need to investigate time and frequency-specific characteristics when examining electrocortical activity during RE. More research is necessary to further explore the acute cortical mechanisms related to resistance exercise. Future research could improve our understanding of acute neural responses to RE and provide insights into mechanism underlying more long-term neuroplastic adaptations to RT.

Approximate simulation of the hysteresis friction of radial shaft seals - Bührmann, Tobias; Magyar, Balázs (Tribologie und Schmierungstechnik)

Investigation of the friction and deformation behaviour of high-speed brakes - Schadomsky, Magnus; Rauhaus, Johann; Blumenthal, Lars; Zimmer, Detmar; Magyar, Balázs (Tribologie und Schmierungstechnik)
<cf:p>Spring-applied brakes are widely used components in industrial drive systems. They provide a braking torque by friction between a mostly organic friction lining and a metallic counter surface. Increasing with decreasing size, they currently achieve speeds of up to 6,000 rpm, which corresponds to a sliding speed in frictional contact of up to 35 m/s. At the same time, there is a trend towards high-speed drives, with speeds of 10,000 rpm and above. So far, little is known about the behaviour of the friction value and torque of conventional spring-applied brakes with low-cost organic friction linings under these operating conditions. For this reason, a test rig was develop - ed that allows testing at sliding speeds of up to 120 m/s with different load inertias. The tests carried out at KAt so far showed that with limited friction work, the conventional spring-applied brake reaches the nominal braking torque at higher sliding speeds. In addition to thermal overload of the friction lining, plastic deformation of the friction bodies can also permanently disrupt the operating behaviour of brakes operated at high sliding speeds. The plastic deformation of the friction discs manifests itself, for example, in a saucer-like shape of the discafs, leading to a reduction in the air gap and causing unwanted changes in the friction conditions. This paper describes the relationship between friction work and friction coefficient in organic linings and the physical mechanism of the deformation process of the friction discs. Based on these possible measures to reduce deformation are explained. </cf:p>

The burdens of sitting on the bench – comparison of absolute and relative match physical load between handball players with high and low court time and implications for compensatory training - Büchel, Daniel; Döring, Michael; Baumeister, Jochen (Journal of Sports Sciences)

Holistische Methode zur elastischen Auslegung von geclinchten Bauteilen - Martin, Sven
Die Auslegung von gefügten Bauteilen ermöglicht die Produktion von Strukturbauteilen, welche teils aus sehr vielen Einzelteilen bestehen und durch eine hohe Anzahl von Fügepunkten verbunden sind. Die Eigenschaften der Einzelteile und die Prozessgrößen in der Fertigung unterliegen Schwankungen, die bei der Auslegung berücksichtigt werden müssen. Um diese Bauteile stets nach der Spezifikation zu liefern, werden die Prozesse gewöhnlich über die gesamte Prozesskette überwacht und das Bauteil überdimensioniert. Treten unvorhersehbare Störungen in der Prozesskette auf, kann das Bauteil nicht mehr weiter produziert werden. Entweder muss die Störung im Prozess behoben werden, was nicht immer möglich ist und die schon teils produzierte Charge muss vernichtet werden, oder der Teil der Prozesskette nach der Störung muss angepasst werden. Dies kann z.B. durch eine Änderungskonstruktion, wie der Anpassung der Fügepunktpositionen und der -anzahl, geschehen. In dieser Dissertation wurde eine Auslegungsmethode zur strukturellen elastischen Auslegung punktgefügter Bauteile entwickelt, mit der eine Anpassungskonstruktion, z.B. auf solche Störungen, möglich ist. Diese Methode basiert auf der Ausnutzung des Einflusses von geometrischen Bauteilgrößen, wie z.B. der Bauteildicke und der Fügepunktpositionierung, von veränderten Fügepunkteigenschaften sowie dem Verständnis zwischen Prozessgrößen und den erzeugten Fügepunkteigenschaften.

Prospective Life Cycle Assessment of Lightweight Structures in Vehicles for On-Demand Mobility Systems - Ostermann, Moritz; Marten, Thorsten; Tröster, Thomas (16th Biennial International Conference on EcoBalance)
Keywords: Life Cycle Sustainability Assessment; Prospective Life Cycle Assessment; Life Cycle Engineering; On-Demand Mobility; Mobility Services

Scenario-based life cycle assessment of vehicle lightweight structures - Ostermann, Moritz; Marten, Thorsten; Tröster, Thomas (Sustainability in Product and Production Engineering)

Das kollektive Gedächtnis im Kanon Flanderns – ein artifizielles und isoliertes Geschichtsbild? - Huybrechts, Yves (Rhein-Maas (Erinnerungskultur – Vielfalt der Perspektiven))

Mut zur fachlichen Expertise im Religionsunterricht! Eine Leseempfehlung für Religionslehrkräfte zu dem exegetischen Grundlagenband von Frankemölle, Hubert: Gott glauben - jüdisch, christlich, muslimisch (Herder, Freiburg 2021) - Garske, Volker (https://schule-hochschule. wir-erzbistum-paderborn.de.news)